2021
DOI: 10.2147/prbm.s340322
|View full text |Cite
|
Sign up to set email alerts
|

How and When Telework Improves Job Performance During COVID-19? Job Crafting as Mediator and Performance Goal Orientation as Moderator

Abstract: Purpose: Literature shows that it is a paradox whether employees can achieve performance in telework, especially during COVID-19. Our aim is to clarify the relationship between telework and employees' job performance through a moderated mediation model. Methods: This study employed two-wave surveys with the aim of reducing the potential risk of common method bias. The 1309 participants of the survey were mainly employees who used telework during COVID-19, and they were mostly in positions such as product desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 67 publications
2
39
2
1
Order By: Relevance
“…Similar to the results of Liu’s study, it is important for employees to improve their job performance by job shaping and setting goals for telecommuting employees’. 16 This result is consistent with our study, which showed the advantages of establishing flexible office hours and developing the social skills of teleworking employees. Troll found that physical conditions and autonomous motivation were significantly correlated with job performance.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the results of Liu’s study, it is important for employees to improve their job performance by job shaping and setting goals for telecommuting employees’. 16 This result is consistent with our study, which showed the advantages of establishing flexible office hours and developing the social skills of teleworking employees. Troll found that physical conditions and autonomous motivation were significantly correlated with job performance.…”
Section: Discussionsupporting
confidence: 92%
“… 2022 ; Ipsen et al. 2021 ; Liu, Wan and Fan 2021 ). On the other hand, studies have found that WFH may lead to employees' lack of supervision, miscommunication, and less organizational commitment (Madell 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple factors influence the success of boundary setting, including the availability of workstation space, number of people in the house, dependents requiring support with remote learning, and are consistent with research 29) from a range of countries during the pandemic. An emerging challenge for organisations is the adoption of new models of WFH post pandemic, based on evidence collected during the pandemic which emphasises the importance of dedicated workspace and ability to work without interruptions, in addition to good quality organisational support to optimise performance and productivity 29,30) .…”
Section: Strategies Implemented To Optimise Wfhmentioning
confidence: 99%